2021
DOI: 10.1007/s00167-021-06709-2
|View full text |Cite
|
Sign up to set email alerts
|

A 2D qualitative movement assessment of a deceleration task detects football players with high knee joint loading

Abstract: Purpose The deceleration (pressing) is a common situational pattern leading to anterior cruciate ligament (ACL) injury in football. Although mainly assessed for performance purposes, a stronger focus on movement quality might support the screening of at-risk athletes. The aim of the present study was to describe a 2D scoring system for the assessment of the deceleration task and to associate it with the knee joint loading (knee abduction moment) evaluated through the gold standard 3D motion captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Furthermore, as the preparatory deceleration steps that have a greater impact on COD performance seem to occur in the sagittal plane, future research should investigate if deceleration capabilities measured during a COD task are associated with performance in that task only, or also with the deceleration capabilities in tasks without a COD. Such findings could lend further support for the use of horizontal acceleration-to-deceleration tasks without a COD for: (1) profiling a player's ability to decelerate rapidly prior to COD, (2) identifying athletes at a heightened risk of injury because of high-impact forces and knee joint loads [98,99] and (3) helping to determine when an athlete is ready to return to sport following injury [100][101][102][103].…”
Section: Braking Ground Reaction Force Magnitudementioning
confidence: 99%
“…Furthermore, as the preparatory deceleration steps that have a greater impact on COD performance seem to occur in the sagittal plane, future research should investigate if deceleration capabilities measured during a COD task are associated with performance in that task only, or also with the deceleration capabilities in tasks without a COD. Such findings could lend further support for the use of horizontal acceleration-to-deceleration tasks without a COD for: (1) profiling a player's ability to decelerate rapidly prior to COD, (2) identifying athletes at a heightened risk of injury because of high-impact forces and knee joint loads [98,99] and (3) helping to determine when an athlete is ready to return to sport following injury [100][101][102][103].…”
Section: Braking Ground Reaction Force Magnitudementioning
confidence: 99%
“…These new findings raise questions whether or not ACL injured athletes with “Typical” BB patterns should be treated differently after surgical stabilization. This sub-group of patients may need a high volume of neuromuscular training and increased attention on movement patterns, particularly related to the promotion to deceleration tasks or cutting mechanics [ 6 , 9 ], which should be implemented in the mid and late-stage rehabilitation process [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 In a study that assessed the reliability of a 2D scoring system compared with 3D motion capture, Di Paolo et al used a deceleration task as the test of choice in their cohort, as sudden deceleration from a frontal sprint is a common scenario for ACL injury. 39 Another study did the same using a 90-degree change of direction at maximum speed. 45 Both motion patterns more closely recreate the conditions in which ACL injury occurs and it is possible that these types of assessments would better guide return to sport decision making and more closely identify athletes at risk of second ACL injury than the widely used criteria of muscle strength and hop tests.…”
Section: Assessment Considerationsmentioning
confidence: 99%
“…While the authors suggest the utility of these assessments as a screening tool, they also recommend future validation studies, which may facilitate the inclusion of these assessments in return to sport criteria. 39 While not objective in nature, patient-reported functional and psychological outcomes play a part in return to sport. Fones et al 46 found that ACL return to sport after injury scores, which include both functional and psychological patientreported outcome measures (PROMs), as well as IKDC scores, were statistically higher in patients who returned to sport than in those who did not.…”
Section: Assessment Considerationsmentioning
confidence: 99%